2014
DOI: 10.1098/rspa.2014.0241
|View full text |Cite
|
Sign up to set email alerts
|

On bifurcations in lifts of regular uniform coupled cell networks

Abstract: A lift of a given network is a network that admits the first network as quotient. Assuming that a bifurcation occurs for a coupled cell system consistent with the structure of a regular network (in which all cells have the same type and receive the same number of inputs and all arrows have the same type), it is well known that some lifts exhibit new bifurcating branches of solutions. In this work, we approach this problem restricting attention to uniform networks, that is, networks that have no loops and no mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Proof. Note that for every positive integer t, the (tq)-ring is a lift of the q-ring [13]. Among these, the direct lifts are the ( pq)-rings, with p prime.…”
Section: Ringsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proof. Note that for every positive integer t, the (tq)-ring is a lift of the q-ring [13]. Among these, the direct lifts are the ( pq)-rings, with p prime.…”
Section: Ringsmentioning
confidence: 99%
“…The result of lemma 4.1 can be extended to valency-1 regular networks. Indeed, these networks have a unique nontrivial strongly connected component, which is a unique q-cycle, with q 1 [13]. Therefore, they have only two types of connected direct lifts: those that result from splitting the q-cycle into a ( pq)-cycle, with p prime, and those that result from splitting exactly one cell into two cells (which is equivalent to adding a unique vertex with 0 outdegree).…”
Section: Ringsmentioning
confidence: 99%
“…Ring networks have been studied, for example, in Ganbat [19] and Moreira [31]. Definition 2.12 A network for which there is a cell c such that, for any other cell d, there is exactly one directed path from c to d is called a directed rooted tree.…”
Section: Definition 29 Letmentioning
confidence: 99%
“…We denote by rings the cycles in the network involving only one edge type, and by the depth the maximal distance of any cell to a ring. Ring networks have been studied, for example, in Ganbat [5] and Moreira [8]. We start by looking at networks having a group structure ( § 7).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that there exists an intrinsic relation between coupled cell systems and coupled cells networks, proving in particular, that robust patterns of synchrony of cells are in oneto-one correspondence to balanced colorings of cells in the network -see [12, theorem 6.5]. Coupled cell networks and coupled cell systems have been addressed, for example, from the bifurcation point of view, [1,5,7,8].…”
Section: Introductionmentioning
confidence: 99%